PENGARUH KINERJA KEPALA DESA TERHADAP PEMBERDAYAAN MASYARAKAT DI DESA TOUNELET KECAMATAN SONDER KABUPATEN MINAHASA - SOEBADI, INDRA; ROMPAS, WELSON; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2018)
abstract: The results of the data analysis show that the hypothesis which states "the performance of the villagehead has a positive effect on community empowerment in Tounelet Village, Sonder District" is acceptable. Thisindicates that the relationship between the two variables can be said quite weak, where the correlationcoefficient obtained by 0.334 with coefficient of determination of 0.112 or 11.2%. This result means that theachievement of community empowerment is also determined by the performance of village head 11,2% whilethe rest equal to 88,8% determined or influenced by other factor. The average performance of the village headand community empowerment in Tounelet Village, Sonder Sub District is in the "moderate" category. Thismeans that both the performance of the village head and the implementation of community empowermentprograms have not been realized optimally. The performance of village heads has a positive and significantimpact on the empowerment of rural communities, especially in Tounelet village, Sonder sub-district. Thismeans that when the village head wants to improve his performance, then the community empowerment of apriority program in the village must be implemented by involving all elements within the village communityitself. The performance of the village head was further enhanced, especially in the community empowermentin Tounelet Village, Sonder Sub District, because it was still categorized as being. In the empowerment of thecommunity should the village government kususnya village chief should pay attention to the community whocan be involved directly in the activities.Keywords: Performance, Community Empowerment